La Sécheresse Dans Le « Quart Nord-Est » De La Côte d’Ivoire: De La Réalité Climatique À La Perception Paysanne - KANGA, Hermann Kouakou; ASSI KAUDJHIS, Joseph P. (European Scientific Journal, ESJ, 2016)
Based on an inquiry on the ground and geostatistics prossessing, this task analyses the problematic of aridity and the perception done by the peasant populations of the ‘’ North -East quarter’’ region of IVORY COAST. We come to know from these analyses that the dryness is a reality in this part of IVORY COAST. Indeed, starting with the indexes of NICHOLSON and MC KEE that is the test of PETTIT and the monthly climatic balance, agricultural and meteorological dryness have been determined to all the studied stations. Mainly the meteorological dryness is much more intensive in this sector of BOUNA and DABAKALA. As to agricultural dryness, it has been heavier in BOUAKE,KATIOLA, DABAKALA and BOUNA respectively. The test of FISHER has justified the variation of the dryness apprehension in the space. Thus, the dryness can be grasped by different ways (four ways) according to the inquired places. However, the peasant populations cannot distinguish the differences between meteorological and agricultural dryness clearly.